A new cell death program regulated by toll-like receptor 9 through p38 mitogen-activated protein kinase signaling pathway in a neonatal rat model with sepsis associated encephalopathy. Issue 12 (20th June 2022) - Zhou, Ruixi; Ying, Junjie; Qiu, Xia; Yu, Luting; Yue, Yan; Liu, Qian; Shi, Jing; Li, Xihong; Qu, Yi; Mu, Dezhi
Abstract: Background: Sepsis, a serious condition with high mortality, usually causes sepsis associated encephalopathy (SAE) that involves neuronal cell death. However, the cell death programs involved and their underlying mechanisms are not clear. This study aimed to explore the regulatory mechanisms of different cell death programs in SAE. Methods: A neonatal rat model of SAE was established by cecal ligation and perforation. Survival rate and vital signs (mean arterial pressure and heart rate) were monitored, nerve reflexes were evaluated, and cortical pathological changes were observed by hematoxylin and eosin staining. The expression of pyroptosis, apoptosis, and necroptosis (PANoptosis)-related proteins, mitogen- activated protein kinase (MAPK), and its upstream regulator toll-like receptor 9 (TLR9) were detected. The expression of TLR9 in neurons was observed by immunofluorescence staining. The ultrastructure of neurons was observed by transmission electron microscope. Results: First, PANoptosis was found in cortical nerve cells of the SAE rats. Meanwhile, the subunits of MAPKs, p38 MAPK, Jun N- terminal kinase, and extracellular signal-regulated kinase (ERK) were activated. After pharmacologically inhibiting each of the subunits, only p38 MAPK was found to be associated with PANoptosis. Furthermore, blocking the p38 MAPK signaling pathway activated necroptosis but inhibited apoptosis and pyroptosis. When necroptosis was pharmacologically inhibited, apoptosis and pyroptosis were reactivated. Finally, we found that the expression of TLR9, a regulator of MAPKs, was significantly increased in this model. After down-regulation of TLR9, p38 MAPK, and ERK signaling pathways were inhibited, which led to the inhibition of PANoptosis. Further analysis found that down-regulation of TLR9 improved the survival rate and reduced the pathological changes in SAE rats. Conclusions: Our study showed that the programs comprising PANoptosis are activated simultaneously in SAE rats. TLR9 activated PANoptosis through the p38 MAPK signaling pathway. TLR9 may work as a potential target for SAE treatment.